(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
The aim of this study was to describe the actions carried out by the project "Liga Acadêmica de EstomatoPatologia (LAEP)," linked to PROEC/UPE, during the COVID-19 pandemic. University extension is an essential component of university education, and in this context, LAEP was founded with the objective of creating a space for discussing lesions and their aspects within Oral and Maxillofacial Pathology and Oral Medicine. The activities developed by LAEP consist of both theoretical and practical moments. In 2022, LAEP activities took place virtually. The participants attended classes, engaged in case discussions, and promoted knowledge dissemination through Instagram, with interactions at the national and international levels. Furthermore, the social event was conducted through YouTube, bringing to the general population a round table discussion on the topic "Oral manifestations of child violence." Therefore, despite the difficulties encountered, it was possible to develop a space to raise awareness in society about the conditions affecting the oral and maxillofacial region, in addition to disseminating knowledge in Oral Medicine and Pathology.